Novelties in Baccharis sect. Caulopterae (Asteraceae: Astereae) - Deble, Leonardo Paz (2014)
A new species – Baccharis tenuiptera – endemic to southern coast of Rio Grande do Sul State (Brazil) is described and illustrated. The new species was previously determined as Baccharis triangularis Hauman; this species, however, is recognized as endemic of central Argentina. A new combination and status is proposed to allied Argentinean taxon Baccharis genistelloides subsp. lorentzii Joch. Müll.